2016
DOI: 10.1016/j.conbuildmat.2016.05.055
|View full text |Cite
|
Sign up to set email alerts
|

Material strength safety factors for the seismic safety assessment of existing RC buildings

Abstract: h i g h l i g h t sSafety factors are proposed to characterize material strength in existing buildings. The uncertainty due to the number of tests and strength variability are considered. The safety factors are compatible with EC8/3 seismic safety assessment methods. Safety factors and survey plans are defined for concrete compressive strength. Safety factors and survey plans are defined for reinforcing steel yield strength. a r t i c l e i n f o b s t r a c tNew material safety factors (CF mat ) are proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The shear strength equation in a review effective voltage that can be deployed ground, until the achievement of equilibrium conditions with regard to boundary safety factor [29], Eq.3.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The shear strength equation in a review effective voltage that can be deployed ground, until the achievement of equilibrium conditions with regard to boundary safety factor [29], Eq.3.…”
Section: Methodsmentioning
confidence: 99%
“…In this program, the value entered (input) is as follows: Dimensions slope elevation, slope length, slope angle in the x and y-axis. Projections slope safety factor analysis using Software Slide 6.0 [29] is shown in Figure 3. Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of the application of these two methods, Kazemi et al proposed a strength estimation formula based on the rebound value [18][19][20][21][22][23], and further studies also reported improved precision in strength estimation through analytical methods [24][25][26][27]. Alwash et al derived the relationship between the compressive strength and ultrasonic pulse velocity [28][29][30], and Phoon et al proposed modifications considering the influence of various materials such as cement and aggregate [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…One of the important factor that affects evaluation of the seismic performance of existing building is the concrete compressive strength (Pereira and Romao, 2016a;2016b). In the literature review, a number of research studies have been performed for investigating the influence of concrete strength on the structural performance.…”
Section: Introductionmentioning
confidence: 99%